1993
DOI: 10.1111/j.1945-5100.1993.tb00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon in the matrices of ordinary chondrites

Abstract: Carbon in the petrologic matrices of a number of ordinary chondrites of groups €3, L, and LL, and of types 3 through 6 was studied with a nuclear microprobe and a Raman microprobe. The majority of the matrices had carbon contents in the narrow range between 0.03 and 0.2 wt%. The carbon content decreased only slightly with increasing petrologic type. Carbonrich coats around troilite and/or metal phases occured in five meteorites. Poorly ordered carbon was found in the matrices. The carbon in the meteorites of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 33 publications
5
33
0
Order By: Relevance
“…It is generally accepted that organic materials are located in the matrices of carbonaceous chondrites (Michel‐Levy and Lautie ; Makjanic et al. ; Brearley ; Pearson et al. ; Abreu and Brearley ; Le Guillou et al.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally accepted that organic materials are located in the matrices of carbonaceous chondrites (Michel‐Levy and Lautie ; Makjanic et al. ; Brearley ; Pearson et al. ; Abreu and Brearley ; Le Guillou et al.…”
Section: Resultsmentioning
confidence: 99%
“…Some associations have suggested a clear organic-inorganic relationship. Nuclear and Raman microprobe data have revealed carbonrich coats around troilite and metal phases (Makjanic et al, 1993), but there has been no suggestion that this is organic matter. Small amounts of carbon have been recognized in the interior of chondrules (Hanon et al, 1998), but two-step laser desorption and laser multiphoton-ionization mass spectrometry has revealed that this carbon is not organic in form (Kovalenko et al, 1991;Zenobi et al, 1989).…”
Section: Organic-inorganic Relationshipsmentioning
confidence: 99%
“…Also, strong is the positive banner at the south end of Velebit, where wind is turning easterly. This northeasterly to easterly wind transition is characteristic of the simultaneously occurring bora in the northern Adriatic and scirocco in the southern Adriatic, which is climatologically a frequent event in winter months (Makjanić 1978).…”
Section: Synoptic Conditions During the Map Iop 15mentioning
confidence: 99%
“…The large part of the existing body of research on bora focuses on the climatology and mesoscale characteristics of this cold, violent, downslope wind (Yoshino 1976;Makjanić 1978;Jurčec 1981). A significant body of work is also devoted to the first in situ observations of the bora conducted during the Alpine Experiment (ALPEX) in 1982 (Smith 1987) and the 2D theory and simulations, supporting the view of bora as a continuously stratified analogue of a hydraulic flow in the transition from a subcritical to a supercritical state (Smith 1985;Klemp and Durran 1987;Bajić 1988;Tutiš 1988;Grubišić 1989;Ivančan-Picek and Vučetić 1990).…”
Section: Introductionmentioning
confidence: 99%